Description of the Factors Behind The Choice Of Alternative Medicine In Breast Cancer Patient - Putri, Ismira Yanti; Indra, Rani Lisa; Lita, Lita (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Introduction: Breast cancer is the number one cancer in Indonesia and number two in the world. One of the factors that influence the cancer mortality rate is the low number of visits by cancer patients to medical experts. Patients prefer alternative treatments that have not been proven that can have an impact on patient survival. Purpose:This study aimed to determine the factors behind the choice of alternative medicine in breast cancer patients. Methods: Descriptive research was conducted on 30 breast cancer patients in one of the government hospitals in the city of Pekanbaru taken by accidental sampling technique. data collection using a questionnaire and analyzed univariately using a frequency distribution table. Results: The results of the study for predisposing factors, found 63.3% of respondents aged > 46 years, good knowledge (100%), have a positive attitude (63.3%), high school education level (63.3%), and work status is working ( 56.7%). for enabling factors, 70% of respondents have easy access to health services and low economic status (86.7%). For driving factors, information related to cancer treatment was obtained from family/friends/neighbors (96.7%). Conclusion & Suggestion: It is hoped that health workers will be more aggressive in providing education about breast cancer treatment, and the public is expected to immediately check with health workers if they feel that there is something unusual in their breasts